الطواحين المائية مظهر من مظاهر العمارة بالمغرب الأوسط من الفتح الاسلامي إلى سقوط الدولة الزيانية(من القرن 1ه إلى القرن 10ه) - فرجاوي بلقاسم (جامعة محمد بوضياف بالمسيلة, 2025)
تناولت هذه الدراسةأحدالجوانبالمعماريةوالاقتصاديةالمهمشةفيالمغرب الأوسط خلال العصر الوسيط وهي الطواحين المائية،مركزةعلىدورها كمظهر من مظاهر العمارة في البلاد،وهذا بالتطرقلنشأتهاوانتشارهاعلىضفافالأنهاربمدنالمغربالأوسط،والكشفعنالوظائفالمتعددةالتيأدتها،منطحنالحبوبإلىالمساهمةفيالحرفوالصناعاتالبسيطة المنتشرة آنذاك. واعتمدنا في هذه الدراسةعلىمصادرمتنوعة،منهاكتبالنوازل،والجغرافيا،والتاريخ العام،لتتبعحضورالطواحينو مجال انتشارها،كماأبرزتالدراسةالعواملالجغرافيةوالتقنيةالتيساعدتعلىازدهارهذهالمنشآت،مؤكدةأنالطاحونةالمائيةكانتأكثرمنمجردمنشأةاقتصادية،بلجزءًامنالبنيةالتحتيةالمتطورةللمدنفي المغرب الأوسط في تلك الحقبة المهمة من التاريخ. This study addresses one of the overlooked architectural and economic aspects of the Central Maghreb during the medieval period: watermills. It focuses on their role as a manifestation of architectural development in the region, exploring their origins and spread along riverbanks in the cities of the Central Maghreb. The study sheds light on the multiple functions these mills performed—from grinding grain to supporting various local crafts and small-scale industries of the time. A wide range of sources was consulted, including books of Nawāzil (Islamic legal responsa), geographical works, and general historical chronicles, to trace the presence and spatial distribution of watermills. Furthermore, the study highlights the geographical and technical factors that contributed to the proliferation of these installations, emphasizing that the watermill was not merely an economic structure but rather an integral component of the urban infrastructure in the Central Maghreb during this significant historical era.